Legal Analysis Of Interbank Business Competition In Lending - Marpol Marpol; Erinaldo Erinaldo (International Asia Of Law and Money Laundering, 2022)
Competition between banks, especially in lending between commercial banks and BPRS can cause unfair business competition, given the ability of commercial banks to capitalize far above the BPRS, which has an impact on losses for BPRS. Business competition can not be avoided both commercial banks and commercial banks and commercial banks with Rural Banks. The problem of business competition between banks can occur due to problems of location, product, type of business and market share. This study focuses on the problems of what is the cause of the emergence of business competition. The research method in this paper is used empirical juridical approach and supported normative juridical research. The results of this study indicate that things that can cause unfair business competition between banks can be caused due to differences in interest rates, bank products and services and bank office network while business competition between BPR and commercial banks occurs in the type of credit distributed to MSMEs and Commercial Bank expansion by opening a branch office in the operational area of BPR on the outskirts of the city is unfair business competition the solution with Law No. 5 of 1999 aims, among others, to realize a conducive climate for healthy business competition arrangements so as to ensure the certainty of equal business opportunities for large businesses, medium businesses and small businesses.